Nutritive value of forages as affected by soil and climatic differences - Richardson, D.; Banbury, Evans E.; Erhart, A.B.; Williams, G.; Smith, E.F.; Loper, D.C.; Adepoju, A.; Harbers, L.H.; Cox, R.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This is the third test to measure differences, if any, in performance of cattle in various parts of Kansas due to location, soil, climate, rainfall and/or local feed. Forty-eight Hereford steer calves from the same herd averaging 475 pounds each were divided as uniformly as possible into four groups of 12 animals. One group was assigned to each of four locations: Colby, Garden City, Manhattan, and Mound Valley. Uniform-size concrete lots with sheds were used at each location. Each group of 12 animals was subdivided into two groups of six. The wintering ration consisted of locally grown sorghum silage (FSla) fed free choice with 5 pounds of locally grown second-cutting alfalfa hay per head daily. At the end of the wintering phase, silage was gradually decreased and removed from the ration. At the same time, locally grown sorghum grain was introduced and gradually increased until the grown sorghum grain was self-fed. Salt was the only added mineral throughout the test. Analyses of the feeds used are show in in table 13.
Keywords: Beef; Forages; Soil; Climate; Silage; Gain